2012
DOI: 10.1111/j.1467-7687.2012.01135.x
|View full text |Cite
|
Sign up to set email alerts
|

Epistemic trust: modeling children’s reasoning about others’ knowledge and intent

Abstract: A core assumption of many theories of development is that children can learn indirectly from other people. However, indirect experience (or testimony) is not constrained to provide veridical information. As a result, if children are to capitalize on this source of knowledge, they must be able to infer who is trustworthy and who is not. How might a learner make such inferences while at the same time learning about the world? What biases, if any, might children bring to this problem? We address these questions w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
95
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 116 publications
(105 citation statements)
references
References 23 publications
6
95
0
Order By: Relevance
“…Given a model of how knowledgeable and naïve (i.e., not knowledgeable) individuals choose actions, it is straightforward to formalize how Learning from human action 19 learners could infer who is knowledgeable (and similarly, who is well-intentioned). Indeed, Shafto et al (2012) propose a model of this problem, and bring it to bear on research on the development of epistemic trust Corriveau, Fusaro, & Harris, 2009;Koenig & Harris, 2005;Pasquini, Corriveau, Koenig, & Harris, 2007). In this literature, children's success in choosing reliable informants is attributed to their ability to monitor which informants are knowledgeable.…”
Section: Summary: Implications Of Goal-directed Actions For Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Given a model of how knowledgeable and naïve (i.e., not knowledgeable) individuals choose actions, it is straightforward to formalize how Learning from human action 19 learners could infer who is knowledgeable (and similarly, who is well-intentioned). Indeed, Shafto et al (2012) propose a model of this problem, and bring it to bear on research on the development of epistemic trust Corriveau, Fusaro, & Harris, 2009;Koenig & Harris, 2005;Pasquini, Corriveau, Koenig, & Harris, 2007). In this literature, children's success in choosing reliable informants is attributed to their ability to monitor which informants are knowledgeable.…”
Section: Summary: Implications Of Goal-directed Actions For Learningmentioning
confidence: 99%
“…For instance, a person may be interested in deceiving or lying, instead of teaching or (cooperatively) communicating. These kinds of goals can be straightforwardly formalized within this framework (Shafto, Eaves, Navarro, & Perfors, 2012;Warner, Stoess, & Shafto, 2011). However, we do not yet have definitive lists of the kinds of goals that are relevant.…”
Section: Summary: Implications Of Goal-directed Actions For Learningmentioning
confidence: 99%
“…Learning about the world happens often in the context of personal interactions; yet these interactions may not always be with helpful or competent individuals who are both able and willing to satisfactorily instruct the learner (Shafto et al, 2012). Because of this, it becomes necessary for learners, particularly young children, to become capable of taking a critical stance toward informants in potentially epistemic situations (Mills, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have linked this social dimension with various informant features, such as intention Vanderbilt et al, 2011), niceness or kindness (Landrum et al, 2013;Lane et al, 2013), and helpfulness (e.g., Shafto et al, 2012). Although research has shown that, for example, children prioritize informant niceness over expertise (Landrum et al, 2013) and intention over accuracy (Liu et al, 2013), it is unclear how children are conceptualizing the HELPFULNESS, EFFORT, AND UTILITY 6 social dimension.…”
Section: Is It the Thought That Counts?mentioning
confidence: 99%
See 1 more Smart Citation